Brain structural properties predict psychologically mediated hypoalgesia in an 8‐week sham acupuncture treatment for migraine - Liu, Jixin (Hum Brain Mapp, 2017)
Neuroimaging studies described brain structural changes that comprise the mechanisms underlying individual differences in migraine development and maintenance. However, whether such interindividual variability in migraine was observed in a pretreatment scan is a predisposition for subsequent hypoalgesia to placebo treatment that remains largely unclear. Using T1‐weighted imaging, we investigated this issue in 50 healthy controls (HC) and 196 patients with migraine without aura (MO). An 8‐week double‐blinded, randomized, placebo‐controlled acupuncture was used, and we only focused on the data from the sham acupuncture group. Eighty patients participated in an 8‐weeks sham acupuncture treatment, and were subdivided (50% change in migraine days from baseline) into recovering (MOr) and persisting (MOp) patients. Optimized voxel‐based morphometry (VBM) and functional connectivity analysis were performed to evaluate brain structural and functional changes. At baseline, MOp and MOr had similar migraine activity, anxiety and depression; reduced migraine days were accompanied by decreased anxiety in MOr. In our findings, the MOr group showed a smaller volume in the left medial prefrontal cortex (mPFC), and decreased mPFC‐related functional connectivity was found in the default mode network. Additionally, the reduction in migraine days after placebo treatment was significantly associated with the baseline gray matter volume of the mPFC which could also predict post‐treatment groups with high accuracy. It indicated that individual differences for the brain structure in the pain modulatory system at baseline served as a substrate on how an individual facilitated or diminished hypoalgesia responses to placebo treatment in migraineurs. Hum Brain Mapp 38:4386–4397, 2017. © 2017 Wiley Periodicals, Inc.